PENINGKATAN EFEKTIVITAS GENERATOR TURBIN GAS DENGAN PENDEKATAN OVERALL EQUIPMENT EFECTIVENESS PADA PT MITRA ENERGI BATAM - riko, suhen suhen; Sirait, Ganda (Computer Science and Industrial Engineering, 2020)
PT MEB a company of electric energy in Batam. With production system integrated system by another, make the operational system machine primary production more complex and challenging. Because it, required control operational management system new and innovative point effectiveness to maintain optimal effectiveness level production so maintain capability of competitive and position company as quality electric producer. Research objectives know the level percentage value effective performance machine production and know causes factor effective performance machine does not maximum. Used the method OEE, cause of performance not maximum know through indicators 3 main categories. As for analysis calculation six big losses be to find out detail kind of waste. The benefits research adds to the literature for readers and writers the future understanding related the topic, give scientific work efforts to improve the effective performance the machine production in the company. Get the value percentage of research conclusion OEE production machine gas turbine generator at 83,49%, so the values still below OEE word class standart. Performance efficiency is major factor most influences the performance machine production not optimum at 88,67%. Analysis six big losses, get the speed losses as major factor the largest losses